Highly Uniform All‐Vacuum‐Deposited Inorganic Perovskite Artificial Synapses for Reservoir Computing. (22nd January 2021) - Chen, Li-Wei; Wang, Wei-Chun; Ko, Shao-Han; Chen, Chien-Yu; Hsu, Chih-Ting; Chiao, Fu-Ching; Chen, Tse-Wei; Wu, Kai-Chiang; Lin, Hao-Wu
Abstract : Uniform Artificial Synapses In article number 2000196, Kai‐Chiang Wu, Hao‐Wu Lin, and co‐workers demonstrate vacuum deposited halide perovskite devices that exhibit very uniform electrical synaptic characteristics. Utilizing these devices in the reservoir computing can simultaneously reduce the circuitry complexity and increase its recognition accuracy with noisy inputs. The findings promise to facilitate the utilization of highly homogeneous perovskite/metal oxide structures in high‐performance neuromorphic computing systems.